2019
DOI: 10.1017/jog.2019.80
|View full text |Cite
|
Sign up to set email alerts
|

Meltwater percolation, impermeable layer formation and runoff buffering on Devon Ice Cap, Canada

Abstract: The retention of meltwater in the accumulation area of the Greenland ice sheet and other Arctic ice masses buffers their contribution to sea level change. However, sustained warming also results in impermeable ice layers or ‘ice slabs’ that seal the underlying pore space. Here, we use a 1-D, physically based, high-resolution model to simulate the surface mass balance (SMB), percolation, refreezing, ice layer formation and runoff from across the high-elevation area of Devon Ice Cap, Canada, from 2001 to 2016. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Our ice slab thicknesses are thicker than the impermeable thickness threshold of at least 1 m noted by Ashmore et al (2020) and overall similar to the observed thickness of Greenland's ice slabs, which can limit or substantially delay meltwater percolation (Charalampidis et al, 2016;Machguth et al, 2016;MacFerrin et al, 2019). Spatially, the radar response associated with refrozen ice slabs in Zone II is widespread (Fig.…”
Section: Zone Iii: Compact Glacier Icesupporting
confidence: 82%
See 1 more Smart Citation
“…Our ice slab thicknesses are thicker than the impermeable thickness threshold of at least 1 m noted by Ashmore et al (2020) and overall similar to the observed thickness of Greenland's ice slabs, which can limit or substantially delay meltwater percolation (Charalampidis et al, 2016;Machguth et al, 2016;MacFerrin et al, 2019). Spatially, the radar response associated with refrozen ice slabs in Zone II is widespread (Fig.…”
Section: Zone Iii: Compact Glacier Icesupporting
confidence: 82%
“…Field-based techniques have expanded our knowledge of melting and refreezing processes in firn (Bell et al, 2008;Sylvestre et al, 2013;Forster et al, 2014;Gascon et al, 2014;Machguth et al, 2016), and their observations are necessary to help validate firn models that are often relied upon for mass balance estimates (Ashmore et al, 2020). Field studies typically utilize some combination of firn cores, snow pits, and ground-based radar (GPR) measurements, which provide in-situ measurements or high resolution remotely sensed observations of the local firn column.…”
mentioning
confidence: 99%
“…This is analogous to the ice lens aggregation mechanism proposed for the growth of ice slabs 9 , but in these interior regions, an extreme melt season can be the key catalyst that initiates this aggregation, rather than a multi-year excess melt. This implies that the frequency of extreme melt seasons relative to the rate at which the long-term melt to accumulation ratio allows new pore space and cold content to regenerate above the most recent melt layer 36 can alter the water storage capacity of near-surface firn and its response to ongoing surface melting in the ice sheet interior. This timescale is critical because Greenland has already experienced five recordingbreaking melt seasons since 2000 17,[37][38][39][40] , with the 2019 season second only to 2012 in total melt extent 40 .…”
Section: Resultsmentioning
confidence: 99%
“…The effective permeability of ice layers and the relation to ice layer thickness is an open question. There is evidence that thick ice layers in firn can be impermeable (Ashmore et al, 2020; Gascon et al, 2013), but meltwater infiltration through ice layers has also been observed or inferred (Ashmore et al, 2020; Humphrey et al, 2012; Machguth et al, 2016). Direct observations are needed to understand these processes and their efficacy with thicker ice layers, as found in the lower percolation zone of Greenland (MacFerrin et al, 2019; Machguth et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which meltwater retention in firn can buffer mass loss and sea level rise is also unclear. Greenland's firn zone covers about 80% of the ice sheet, but refrozen near‐surface ice layers have the potential to act as impermeable barriers, redirecting meltwater percolation into runoff (Ashmore et al, 2020; Gascon et al, 2013; MacFerrin et al, 2019; Noël et al, 2017). In the percolation zone, firn densification associated with warming and refreezing is also leading to a loss of available pore space, imposing further limits on meltwater storage capacity as melting progresses inland (Vandecrux et al, 2019).…”
Section: Introductionmentioning
confidence: 99%